2017
DOI: 10.1371/journal.pntd.0005274
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequence Analysis of Salmonella Typhi Isolated in Thailand before and after the Introduction of a National Immunization Program

Abstract: Vaccines against Salmonella Typhi, the causative agent of typhoid fever, are commonly used by travellers, however, there are few examples of national immunization programs in endemic areas. There is therefore a paucity of data on the impact of typhoid immunization programs on localised populations of S. Typhi. Here we have used whole genome sequencing (WGS) to characterise 44 historical bacterial isolates collected before and after a national typhoid immunization program that was implemented in Thailand in 197… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…As the filtering criteria remain the same, the number of SNPs for all Bangladesh isolates is relatively low compared to the global or multicountry context ( 25 27 ) but is similar to country-specific data. For example, 1,850 SNPs were detected in isolates from Thailand ( n = 44) and 2,187 SNPs in isolates from Nepal ( n = 198) ( 29 , 39 ). The wgSNP-MLT data showed distinct differentiation of all genotypes, much like the data from the cgMLST-UPGMA tree, except the latter lacked clear inferences for different H58 lineages ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As the filtering criteria remain the same, the number of SNPs for all Bangladesh isolates is relatively low compared to the global or multicountry context ( 25 27 ) but is similar to country-specific data. For example, 1,850 SNPs were detected in isolates from Thailand ( n = 44) and 2,187 SNPs in isolates from Nepal ( n = 198) ( 29 , 39 ). The wgSNP-MLT data showed distinct differentiation of all genotypes, much like the data from the cgMLST-UPGMA tree, except the latter lacked clear inferences for different H58 lineages ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, intra-near-clade/DTU population genetics in T. cruzi calls for additional studies. Although present data support the Russian doll hypothesis in T. cruzi for all cases conveniently explored, data on T. cruzi intra-near-clade genomic diversity still are scarce by comparison with Leishmania (Imamura et al, 2016) and bacteria (Alnajar and Gupta, 2017;Dyson et al, 2017). Future genomic studies on T. cruzi intra-near-clade population genetics should take as models such approaches based on fine typing using thousands of SNP markers.…”
supporting
confidence: 47%
“…Paratyphi A, B, and C. A recent study that conducted whole-genome sequencing analysis of typhoidal Salmonella isolates noted that most indigenous strains of S. Typhi were depleted following the mass vaccination campaigns of the 1970s. 16 This analysis also indicated that recent strains of S. Typhi are closely related to the strains isolated from neighboring countries such as Laos and Cambodia, which implies that the transmission of indigenous strains is not responsible for causing typhoid in Thailand. 16 Typhoid incidence can potentially be further curbed by using the robust surveillance system in place to improve traveler and migrant screening and, therefore, reduce imported cases of typhoid fever from neighboring endemic countries.…”
Section: Discussionmentioning
confidence: 75%